CATEGORY SHIFTS AND ITS QUALITY IN “TO ALL THE BOYS: ALWAYS AND FOREVER” MOVIE SUBTITLES - Riskita, Renna; Zuhron, Zuhron (Universitas Putera Batam, 2022)
This research aimed to analyze Category shifts; Structure-shift, Class-shift, Unit shift, and Intra-system by Catford (1965) in female-lead utterances in To All The Boys: Always and Forever (2021) movie subtitles, to identify the most dominant shift and the quality of translation used quality assessment of translation theory by Nababan (2012). The descriptive-qualitative method is applied to analyze the data. The data was obtained by the English and Indonesian subtitles. The analysis identified 317 shifts in the data which were then divided according to 4 types of Category shifts. The results showed all of the Category shits were found in the data with the unit shift as the most dominant category shift with a total of 165 data (52%), structure shift with 64 data (20%), intra-system shift with 51 (16%), and the less dominant data is class shift with 37 data (12%). The quality assessment of translations pointed out that 7 data were scored as less accurate. and 1 data each for inaccurate, inacceptable, and unreadable. The data remains were high-scale accuracy, acceptancy, and readability. These results indicated that the occurrence of category shifts is important to achieve naturalness in translation.